A nationwide study of children and adolescents with pneumonia who visited Emergency Department in South Korea in 2012 - Chang Hyu Lee; Youn Kyoung Won; Eui-Jung Roh; Dong In Suh; Eun Hee Chung (Korean Pediatric Society, 2016)
PurposeAcute respiratory infection, particularly pneumonia, is the most common cause of hospitalization and death among children in developing nations. This study aimed to investigate the characteristics of children and adolescents with pneumonia who visited Emergency Department (ED) in South Korea in 2012.MethodsWe analyzed National Emergency Department Information System (NEDIS) records from 146 EDs in South Korea for all pediatric patients aged ≤18 years who were diagnosed with pneumonia between January and December 2012.ResultsAmong 38,415 subjects, the male-to-female ratio was 1:0.8. Patients aged <12 months comprised 18.0% of the study population; those aged 1 to 3 years, 54.4%; those aged 4 to 6 years, 16.8%; those aged 7 to 12 years, 7.4%; and those aged 13 to 18 years, 3.4%. Presentation rates were highest in April, followed by January, March, and May. The hospital admission rate was 43.5%, of which 2.6% were in intensive care units. The mortality rate was 0.02%. Based on the International Classification of Diseases, 10th Revision, diagnostic codes, the types of pneumonia according to cause were viral pneumonia (29.0%), bacterial pneumonia (5.3%), Mycoplasmal pneumonia (4.5%), aspiration pneumonia (1.3%), and pneumonia of unknown origin (59.3%).ConclusionDespite the limited data due to the ED data from the NEDIS lacking laboratory results and treatment information, this study reflects well the outbreak patterns among children and adolescents with pneumonia. Our results provide a basis for future studies regarding ED treatment for children and adolescents with pneumonia.